An exploratory study of the FinTech (Financial Technology) education and retraining in UK. Issue 2 (2nd September 2019) - Sung, Anna; Leong, Kelvin; Sironi, Paolo; O'Reilly, Tim; McMillan, Alison
Abstract : Purpose: The purpose of this paper is to explore two identified knowledge gaps: first, the identification and analysis of online searching trends for Financial Technology (FinTech)-related jobs and education information in UK, and second to assess the current strength of the FinTech-related job distribution in terms of job titles and locations in UK, job market in UK and what is required to help it to grow. Design/methodology/approach: Two sets of data were used in this study in order to fill the two identified knowledge gaps. First, six years' worth of data, for the period from September 2012 to August 2018 was collected from Google Trends. This was in the form of search term keyword text. The hypothesis was designed correspondingly, and the results were reviewed and evaluated using a relevant statistical tool. Second, relevant data were extracted from the "Indeed" website (www.indeed.co.uk ) by means of a simple VBA programme written in Excel. In total, the textual data for 500 job advertisements, including the keyword "FinTech", were downloaded from that website. Findings: The authors found that there was a continuously increasing trend in the use of the keyword "fintech" under the category "Jobs and Education" in online searching from September 2012 to August 2018. The authors demonstrated that this trend was statistically significant. In contrast, the trends for searches using both "finance" and "accounting" were slightly decreased over the same period. Furthermore, the authors identified the geographic distribution of the fintech-related jobs in the UK. In regard to job titles, the authors discovered that "manager" was the most frequently searched term, followed by "developer" and "engineer". Research limitations/implications: Educators could use this research as a reference in the development of the portfolio of their courses. In addition, the findings from this study could also enable potential participators to reflect on their career development. It is worth noting that the motivations for carrying out an internet search are complex, and each of these needs to be understood. There are many factors that would affect how an information seeker would behave with the obtained information. More work is still needed in order to encourage more people to enter to the FinTech sector. Originality/value: In the planning stage prior to launching a new course educators often need to justify the market need: this analysis could provide a supporting rationale and enable a new course to launch more quickly. Consequently, the pipeline of talent supply to the sector would also be benefitted. The authors believe this is the first time that a study like this had been conducted to explore specifically the availability and opportunities for FinTech education and retraining in UK. The authors anticipate that this study will become the primary reference for researchers, educators and policy makers engaged in future research or practical applications on related topics.